2021
DOI: 10.3390/gels8010021
|View full text |Cite
|
Sign up to set email alerts
|

Application of Gelatin Composite Coating in Pork Quality Preservation during Storage and Mechanism of Gelatin Composite Coating on Pork Flavor

Abstract: Gelatin coating is an effective way to prolong the shelf life of meat products. Aiming at solving the problem of flavor deterioration during the storage of pork at room temperature, pork coating technology was developed to preserve the pork at 25 °C, and the comprehensive sensory analysis of vision, touch, smell, and taste was used to study the effect of coating on preservation of pork flavor. Herein, uncoated (control) and coated pork samples (including gelatin coating and gelatin coating incorporated with gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…It was shown that by adding garlic essential oil to gelatin-chitosan edible films, garlic molecules interact with gelatin-chitosan molecules to form hydrophobic interactions, replacing the intermolecular hydrogen bonding between gelatin-chitosan molecules ( Handayasari et al, 2019 ). Li et al, 2022 coated preserved fish meat with gelatin films and ginger essential oil-gelatin films respectively, the results showed that under the same conditions the ginger essential oil-gelatin coated group had significantly slower changes in fish weight loss rate, color, and other changes, the flavor was closer to that of fresh fish. The addition of essential oils to gelatin films enhanced the antibacterial and antioxidant properties of the films.…”
Section: Mechanisms Of Interactions Between Edible Film Functional In...mentioning
confidence: 93%
“…It was shown that by adding garlic essential oil to gelatin-chitosan edible films, garlic molecules interact with gelatin-chitosan molecules to form hydrophobic interactions, replacing the intermolecular hydrogen bonding between gelatin-chitosan molecules ( Handayasari et al, 2019 ). Li et al, 2022 coated preserved fish meat with gelatin films and ginger essential oil-gelatin films respectively, the results showed that under the same conditions the ginger essential oil-gelatin coated group had significantly slower changes in fish weight loss rate, color, and other changes, the flavor was closer to that of fresh fish. The addition of essential oils to gelatin films enhanced the antibacterial and antioxidant properties of the films.…”
Section: Mechanisms Of Interactions Between Edible Film Functional In...mentioning
confidence: 93%
“…In this regard, it has been reported that the increase in surface roughness was attributed to the migration of oil droplets towards the film surface and the evaporation of essential oils during the film drying process [41]. Also, the heterogeneity of the film improves the antimicrobial properties of the film and helps the release of essential oils.…”
Section: Sem and Xrdmentioning
confidence: 99%
“…Gelatin is a natural peptide mixture consisting of several amino acids . It has been widely used in food processing, green ecology, medical health, and other fields because of its advantages of good biocompatibility, biodegradability, and non-toxicity. The gelatin hydrogels, which can easily be formed from their aqueous solutions when cooled to room temperature, have attracted a plenty of attention . However, hydrogels tend to freeze at subzero temperatures, which will cause the degradation of their performances and hence restrict the low-temperature applications. , Therefore, improving their anti-freezing properties is an important issue in hydrogels.…”
Section: Introductionmentioning
confidence: 99%